Macrozoobenthos as a Bioindicator for Water Quality on the Coast of Padang City, West Sumatra - Asma Ul Husna Putri; Afrizal Tanjung; Efriyeldi Efriyeldi (Jurnal Natur Indonesia, 2024)
The research was carried out in January 2024 at the coastal waters of Padang City, West Sumatera Province. This research aims to determine the structure of the macrozoobenthos community as a bioindicator of water quality on the beaches of Padang City. Purposive sampling was used to get the sample, and then data was analyzed using FBI methods. (Family Biotic Index). The research results using FBI calculations show that Station 1 is in a good category with a score of 4.73, Station 2 is in the good category with a score of 4.71, and Station 3 is in the relatively poor category with a score of 6. Thus, the water quality based on macrozoobenthos as bioindicators of the coastal waters of Padang City, with an FBI value, was found to have an average of 5.14, which falls into the moderate category